measuring the effect of human capital management and corporate values to corporate performance: case study in bank bjb - Pratiwi, Amelia; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2016)
Abstract - In 2010, bank bjb initialized IPO and become the very first governance-owned bank that go public. With this initiative, bank bjb sees the necessary to transform not only their system, but also their values and talents to support their business growth. The need to transform push bank bjb to understand what factor that affecting their performance. With this very reason, researcher conduct a research to measure performance based on HCM factor and corporate values factor in bank bjb. Researcher conducts interview and questionnaire to gather the data with total sample of 150 employees. The data collected was measured by using partial least square (PLS) and the result is contradictive with general theory of human capital management where HCM supposed to be affecting performance positively, further explanation will be discussed in analysis result. With the affection of 21.7%, there is still 78.3% other factor that still unexposed or unknown by researcher. Â Keyword: Human capital management (HCM), corporate values, performance.Â